Time-resolved Fourier transform infrared emission spectroscopy of CO ∆v = 1 and ∆v = 2 extended bands in the ground X1Σ+ state produced by formamide glow discharge. (March 2021) - Pastorek, Adam; Civiš, Svatopluk; Clark, Victoria H.J.; Yurchenko, Sergei N.; Ferus, Martin
Highlights: An extension to the knowledge of ∆ v  = 1 and ∆ v  = 2 bands of carbon monoxide in the ground state, measured up to v  = 30 for ∆ v  = 1 and up to v  = 24 for ∆ v  = 2 band. Dunham parameters obtained by fitting as well as comparison to other authors. Non-LTE model to describe the intensity pattern of the ∆ v  = 1 and the ∆ v  = 2 bands of 12 C 16 O experimental spectra. Abstract: This paper presents an extension to our knowledge of ∆ v  = 1 and ∆ v  = 2 bands of carbon monoxide in the ground state, measured by Fourier transform infrared spectroscopy of glow discharge of formamide-nitrogen mixture. Lines in declared bands are measured up to v  = 30 for ∆ v  = 1 and up to v  = 24 for ∆ v  = 2 band, by use of both InSb and MCT detectors, which have not been measured in the laboratory before. Dunham parameters obtained by fitting our lines are presented as well as comparison to other authors. The paper also demonstrates the interesting impossibility of sufficient population of ∆ v  = 2 band of CO when only pure CO is used in the glow discharge, instead of formamide-based mixture. Additionally, we present a non-LTE model to describe the intensity pattern of the ∆ v  = 1 and the ∆ v  = 2 bands of 12 C 16 O experimental spectra by simulating the corresponding non-LTE vibrational populations of CO.